Model Pemberdayaan Masyarakat Dalam Pencegahan Penyalahgunaan Narkoba di Provinsi Riau - Jeihany Anggrilla Safarani; Agus Adriyanto; Herlina Juni Risma Saragih (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
Prevention of drug abuse is part of the implementation of P4GN by BNNP Riau. This program increases public awareness of the threats and dangers of drugs and supports national security which is correlated with improving people's welfare. P4GN is manifested through various sub-programs and empowerment with a directive approach. The realization of “desa bersinar”, the implementation of alternative empowerment and improvement of life skills, and the use of media by the local government with the assistance of the BNNP Riau directly have an impact on reducing the number of drug use. This study uses a qualitative approach located in Riau Province. Data collection uses interviews and documentation which are then analyzed to draw conclusions and have been verified. Test the validity of the data using source triangulation. The results of the study indicate that P4GN which is implemented through the role of the regional government, especially BNNP Riau, is collaboratively carried out with several real activities that are directed and systematized. Various anti-drug activities and campaigns using the media are BNNP's instruments in changing people's mindsets to stay away from drugs. The program carried out runs with intervention, especially the community empowerment as the center of IBM cadres. The implementation of P4GN can increase productivity which leads to prosperity and a conducive state condition so as to assist the government in maintaining national security.